Febuxostat in patients with hyperuricemia and gout: is the nephroprotective effect real? - M. S. Eliseev; Ya. I. Kuzmina (Современная ревматология, 2024)
Hyperuricemia (HU) and gout are independent risk factors for chronic kidney disease (CKD). Worldwide, the increasing prevalence of CKD leads to a deterioration in the quality and duration of life of patients and an increase in mortality. If HU plays a significant role in the development of renal failure, then lowering high uric acid (UA) levels should theoretically contribute to the improvement of kidney function. The main method of lowering UA levels is administration of a urate-lowering therapy – xanthine oxidase (XO) inhibitors. The nephroprotective effect of one of the XO inhibitors, febuxostat has been demonstrated in animal models.The article analyzes the currently available data on the use of febuxostat in patients with HU and gout and different levels of renal function impairment and discusses the possible mechanisms of the drug's nephroprotective effect.